2011
DOI: 10.1016/j.joca.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the safety and efficacy of tanezumab in Japanese patients with moderate to severe osteoarthritis of the knee: a randomized, double-blind, dose-escalation, placebo-controlled study

Abstract: Tanezumab was safe and generally well tolerated and may improve pain symptoms in Japanese patients with moderate to severe osteoarthritis of the knee. CLINICALTRIALS.GOV IDENTIFIER: NCT00669409.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 20 publications
2
71
0
1
Order By: Relevance
“…Tanezumab, a humanized monoclonal antibody for NGF, provided significant pain relief for OA patients when administered alone or as an adjunct therapy [85][86][87][88][89][90][91]. Conversely, the direct application of NGF caused hyperalgesia and allodynia in both rats [92] and humans [93].…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…Tanezumab, a humanized monoclonal antibody for NGF, provided significant pain relief for OA patients when administered alone or as an adjunct therapy [85][86][87][88][89][90][91]. Conversely, the direct application of NGF caused hyperalgesia and allodynia in both rats [92] and humans [93].…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…Currently, there are no approved biological therapies for patients with OA. Recent studies showed significant improvement in pain and function of knee OA with tanezumab; however, it should be mentioned that mild to moderate AEs occurred [32][33][34][35].…”
Section: Tanezumabmentioning
confidence: 99%
“…During the neonatal period, NGF supports development of the sensory neurons; in adults, NGF is essential in raising awareness of the nociceptor function of neurons with the onset of pain and hyperalgesia in chronic pain. This function may be observed after injury and inflammation, when NGF expression ultimately increases, including in patients with OA, who also express high levels of NGF in their joints [32][33][34][35].…”
Section: Tanezumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal evidence of AEs with repeat injections was shown. Nagashima et al [ 129 ] investigated the use of tanezumab in 83 patients with moderate and severe OA -all AEs were considered mild to moderate in severity. Overall, the use of tanezumab was considered safe and well tolerated.…”
Section: Tanezumab: Ngf Blockermentioning
confidence: 99%